The technology of skill formation - Flavio Cunha; James Joseph Heckman (Institute for the Study of Labor (IZA), 2007)
This paper develops a model of skill formation that explains a variety of findings established in the child development and child intervention literatures. At its core is a technology that is stage-specific and that features self productivity, dynamic complementarity and skill multipliers. Lessons are drawn for the design of new policies to alleviate the consequences of the accident of birth that is a major source of human inequality.
urn:nbn:de:101:1-20080425464
Keywords: 330; Humankapital; Qualifikation; Bildungsfinanzierung; Familie; Kinderbetreuung; Theorie